Milk production in the post-genomic era - Frajman, Polona (Acta agriculturae Slovenica, 2004)
Milk plays an important role in human nutrition. Nowadays, dairy industry is oriented in the production of increasing number of different milk products and technological properties of milk are gaining more and more attention. Introduction of recombinant DNA technologz in the early 1970 and development of molecular genetics enabled studies of the organization of milk protein genes and mechanisms involved in their expression. Genome research in farm animals was oriented in production of low-density genetic maps with the emphasis on the genetic variation in some functionally important regions. In the public databases, 1598 cattle genes have already been mapped and partially sequenced by the end of 2003. In addition, numerous quantitative trait loci (QTL) were mapped for economically important traits. Typical examples include milk yield and milk composition in dairy cattle. The availability of genomic DNA sequences for a number of potential candidate genes with an impact on production traits allowed construction of cattle genome microarrays. Functional studies of milk protein genes revealed the impact of different genetic variants on technological properties of milk. Genomics approach thus offers an entirely new way to identify complex interactions among milk protein genes other genes involved in milk production and elucidation of the complex regulatory network allowing efficient milk production in the mammary gland.
Keywords: mlekarstvo; mleko; proizvodnja; tehnološke lastnosti; genetics; genetika; biokemija; molekularna genetika; genom